SUMPAH PEGAWAI NEGERI SIPIL DALAM PERSPEKTIF HUKUM ISLAM - Siregar, Hamka (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: Civil Servants Oath in the Perspective of Islamic Law. In Indonesia, all employees working for the government or other formal organizations are required to take an oath of office prior to undertaking duties. The implementation of the oath are arranged in a number of regulations, ranging from Government Regulations, Presidential Regulations, to Ministerial Regulations. The oath-taking was also conducted before a person occupies a particular position. In the perspective of Islamic law, the oath-taking is also known particularly in court. God condemns the perpetrators of perjury or who do not implement the contents of the oath as it is stated in several verses of the Koran, such as Ali Imran [3]: 77. Ironically, the rule does not have significant effects on the reduction of abuse of power in this country. This research is motivated by such a phenomenon.Keywords: oath of office, Civil Servants Abstrak: Sumpah Pegawai Negeri Sipil dalam Perspektif Hukum Islam. Di Indonesia, semua karyawan yang akan bekerja untuk pemerintah diharuskan untuk melakukan sumpah jabatan sebelum mereka melaksanakan tugas. Pelaksanaan sumpah tersebut diatur dalam sejumlah peraturan, mulai dari Peraturan Pemerintah, Peraturan Presiden, dan Peraturan Menteri. Pengambilan sumpah juga dilaksanakan sebelum seseorang menduduki posisi/jabatan tertentu. Dalam perspektif hukum Islam, pengambilan sumpah juga dikenal khususnya untuk perkara di pengadilan. Allah mengutuk pelaku sumpah palsu atau yang tidak melaksanakan isi sumpahnya seperti dinyatakan dalam beberapa ayat Alquran antara lain Ali Imrân [3]: 77. Ironisnya, aturan tersebut tidak memiliki pengaruh yang signifikan terhadap pengurangan potensi penyalahgunaan kekuasaan di negeri ini. Penelitian ini dilatarbelakangi oleh fenomena tersebut.Kata Kunci: sumpah jabatan, Pegawai Negeri Sipil